Rancang Bangun Alat Kontrol Aliran Fluida Untuk Mensimulasikan Hukum Kontinuitas Sebagai Media Pembelajaran Fisika - Jesi Pebralia (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2018)
This study aims to create a fluid flow control to simulate continuity law as a media for physics learning. Fluid flow control is designed using a digital devices, consist of two main components: Arduino Uno microcontroller and a water flow sensor, that is systematically designed. This study produces a valid fluid flow control to simulate the Continuity Law which can be used as a media for physics learning. Key words: Fluid flow, Arduino Uno, water flow sensor, Continuity Law.